2011
DOI: 10.1182/blood-2011-02-338582
|View full text |Cite
|
Sign up to set email alerts
|

Platelet CD36 surface expression levels affect functional responses to oxidized LDL and are associated with inheritance of specific genetic polymorphisms

Abstract: CD36 modulates platelet function via binding to oxidized LDL (oxLDL), cell-derived microparticles, and thrombospondin-1. We hypothesized that the level of platelet CD36 expression may be associated with inheritance of specific genetic polymorphisms and that this would determine platelet reactivity to oxLDL. Analysis of more than 500 subjects revealed that CD36 expression levels were consistent in individual donors over time but varied widely among donors (

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
86
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 93 publications
(94 citation statements)
references
References 50 publications
(68 reference statements)
8
86
0
Order By: Relevance
“…The rs1761665 SNP, in particular, is in strong LD with promoter SNPs previously shown to influence monocyte and platelet CD36 (58,59). Several of the promoter SNPs we identified here lie in close proximity to validated binding sites for PPAR and to methylation sites that associate with CD36 mRNA levels (Fig.…”
Section: 11supporting
confidence: 51%
“…The rs1761665 SNP, in particular, is in strong LD with promoter SNPs previously shown to influence monocyte and platelet CD36 (58,59). Several of the promoter SNPs we identified here lie in close proximity to validated binding sites for PPAR and to methylation sites that associate with CD36 mRNA levels (Fig.…”
Section: 11supporting
confidence: 51%
“…Notable exceptions have been reported by Himoto et al (25) and García-Monzón et al (26) who identified even lower sCD36 concentrations compared to those from the current study (Table IV). This variation could be population-specific as cellular CD36 expression may be associated with the inheritance of specific CD36 gene polymorphisms (27,28). Additionally, cellular CD36 expression can be affected by other factors including fat intake (29) and blood glucose levels (30).…”
Section: Discussionmentioning
confidence: 99%
“…Triolein and oleic acid were added at varying concentrations to double distilled water. Concentrations used ranged from 0.0009 w/v% to 5 w/v% for oleic acid and from 0.006 w/v % to 31.7w/v % for triolein and were prepared in quarter-log dilution steps. All preparations were mixed with 5% (w/v) Gum Arabica (AEP Colloids, Hadley, NY) and white food colorant was added to produce perceptually identical viscosity and color between oil and control samples.…”
Section: Preparation Of Oleic Acid and Triolein Emulsions Preparationmentioning
confidence: 99%